MWCNTs/Cellulose Hydrogels Prepared from NaOH/Urea Aqueous Solution with Improved Mechanical Properties - Yingpu Zhang; Rong Huang; Si Peng; Zhaocheng Ma (Journal of Chemistry)
Novel high strength composite hydrogels were designed and synthesized by introducing multiwalled carbon nanotubes (MWCNTs) into cellulose/NaOH/urea aqueous solution and then cross-linked by epichlorohydrin. MWCNTs were used to modify the matrix of cellulose. The structure and morphology of the hydrogels were characterized by Fourier transform infrared (FT-IR) spectroscopy, high resolution transmission electron microscopy (HR-TEM), and scanning electron microscopy (SEM). The results from swelling testing revealed that the equilibrium swelling ratio of hydrogels decreased with the increment of MWCNTs content. Thermogravimetric analysis (TGA) and dynamic mechanical analysis (DMA) results demonstrated that the introduction of MWCNT into cellulose hydrogel networks remarkably improved both thermal and mechanical properties of the composite hydrogels. The preparation of MWCNTs modifiedcellulose-based composites with improved mechanical properties was the first important step towards the development of advanced functional materials.